Hypovitaminosis D and hyperparathyroidism: Effects on bone turnover and bone mineral density among perinatally HIV-infected adolescents - Sudjaritruk T. (2017)
© 2016 Wolters Kluwer Health, Inc. All rights reserved. Objectives: The impact of hypovitaminosis D and secondary hyperparathyroidism on bone mineral density (BMD) in the setting of pediatric HIV infection remains unclear. This study aimed to determine the prevalence of hypovitaminosis D and hyperparathyroidism and their effects on bone turnover and BMD among HIV-infected adolescents in Southeast Asia. Design: A multicenter, cross-sectional study evaluating bone health and vitamin D metabolism in HIV-infected adolescents in Thailand and Indonesia. Methods: Perinatally HIV-infected adolescents aged 10-18 years on antiretroviral therapy with virologic suppression were enrolled. Serum 25-hydroxyvitamin D, intact parathyroid hormone, and bone turnover markers (C-terminal cross-linked telopeptide of type I collagen and procollagen type I amino-terminal propeptide) were assessed; serum 25-hydroxyvitamin D less than 20ng/ml and intact parathyroid hormone more than 65pg/ml were defined as hypovitaminosis D and hyperparathyroidism, respectively. Lumbar spine (L2-L4) BMD Z-score-2 or less was defined as low BMD. Results: Of 394 adolescents, 57% were women. The median age [interquartile range (IQR)] was 15.0 (13.3-16.9) years. The prevalence of hypovitaminosis D, hyperparathyroidism, and both conditions were 21% [95% confidence interval (CI): 17-25%] , 17% (95% CI: 13-20%), and 5% (95% CI: 3-7%), respectively. Adolescents with hypovitaminosis D and secondary hyperparathyroidism had the highest median bone resorption (C-terminal cross-linked telopeptide of type I collagen: 1610 vs. 1270ng/l; P=0.04) and bone formation (procollagen type I amino-terminal propeptide: 572 vs. 330μg/l; P=0.02) markers, and the greatest proportion of low BMD (42 vs. 15%; P=0.01) compared with the rest of the cohort. Conclusion: Hypovitaminosis D complicated with secondary hyperparathyroidism was associated with increased bone turnover and bone loss. Early treatment of hypovitaminosis D before hyperparathyroidism occurs may be important to prevent bone mass deterioration.